THE EFFECT OF PERFECTIONISM ON FEAR OF FAILURE IN BOARDING SCHOOL STUDENTS - Surahman Surahman; Moh Fauzil Adhim (Universitas Pendidikan Indonesia, 2022)
Fear of failure is a motive to avoid failure and shame or humiliation caused by failure. Fear of failure has consequences in achieving goals or weakening efforts. In some cases, fear of failure impacts mental health and student achievement. One of the factors influencing the fear of failure is perfectionism. This study aimed to determine the influence of perfectionists on the fear of failure in boarding school students. The study participants comprised 338 boarding school students (185 boys; 135 girls) aged 14-17 years. The research instruments used are the Frost Multidimensional Perfectionism Scale (MPS-F) to measure perfectionists and the Fear of Failure in Learning Scale (FOFL) to measure fear of student failure. A simple linear regression analysis showed that perfectionists could predict fear of failure (R = 0,477; R² = 0,277; p 0,05). The practical contribution of perfectionists to fear of failure was 27,7%. This finding shows that fear of failure is a problem for students affected by perfectionists.